Exploring interactions between performance and efficiency among junior female basketball players: a canonical analysis approach - Jelicic, M.; Jelaska, G.; Stankovic, M.; Capric, I. (Journal of Physical Education and Sport, 2023)
One of the most crucial functions for basketball coaches is strategized practice sessions, based on the demands of the competition. The aim of this research was to determine relations of situational performance and efficiency among junior female basketball players. In accordance with the aim, the research was conducted on a sample of 48 female players and each of the players played for more than 8min. per game. They were measured in 6 variables of situational performance and in 12 variables of situational efficiency. Situational performance variables were measured and an average of 3 matches was taken into consideration. There were no great variations of values within each variable of situational performance or situational efficiency considering that this is a elite sample of female participants. Correlation between the first set of variables of situational efficiency and the first factor of the set of variables of situational performance is statistically significant. An insight into the factorial structure of situational efficiency variables led to the conclusion that the extracted factor can be called the factor of general situational efficiency. Using canonical correlation analysis, a statistically significant correlation (CanR=0.912; p=0.047), which provided an in-depth insight into the complex interactions of performance and efficiency of elite basketball female players in competitive conditions, was identified. Study clearly indicated the correlation between the variables of situational efficiency and of situational performance. The results of this study may give coaches important information regarding planning and programming of contemporary technical and tactical as well as training programmes for junior female basketball players